Pengembangan Model Manajemen Kearsipan Berbasis Web dalam Peningkatan Pelayanan Pembelajaran di Smk At-Taufiqiyah Bluto Sumenep (NUMADURA: Journal of Islamic Studies, Social, and Humanities, 2022)
This development research aims to produce a web-based archive management model product, to make it easier for the head of the administrative section to organize, search, and maintain the security of school archives. In addition, it can make it easier for principals to monitor the archiving process, and provide an archive of learning tools for teachers so that if needed it will make it easier for teachers to access them. This study uses a waterfall development model (Waterfall) through the stages of planning, modeling, construction, and delivery of the system/software to users. The results of the percentage on the development of the archival management model system during the trial of the system expert obtained a percentage of 100%, the design expert was 95.4%, and the head of the system. TU 89%, TU staff 93.8%, school principals 94%, and the results of the trial 12 teachers obtained a percentage of 87%. Judging from the percentage of all trials, the records management model system is included in the "very feasible" qualification. The test results prove that the product development of a web-based archive management model system can be used as a means to help manage, monitor archives, and provide a database for storing online learning tools at SMK At-Taufiqiyah. The existence of this archival management model system also makes it easier for schools to achieve the archive management function.